Analysis of the Vision and Mission of Jabal RahmAnalysis of the Vision and Mission of Jabal Rahmah Kindergarten in the Education Programah Kindergarten in the Education Program - Banurea, Alinuddin; Pradana, M. Nata; Mawaddah, Mawaddah; Paramita, Nadya; Aurelia, Nayla; Nurjarina, Nurjarina; Al Denis, Siti Diva; Alvingkan , Syndy (Educational Studies and Research Journal, 2024)
The vision and mission of an institution are certainly very important in designing the program that an institution wants to achieve. Because with the vision and mission that has been created. So, each institution will focus on implementing what the institution's goals are. This research aims to describe the vision and mission of the Jabal Rahmah Mulia Kindergarten, Jabal Rahmah Mulia Education Foundation, which is considered successful in directing the education system. Data collection in research uses a descriptive qualitative approach. The research results show that this educational institution is designed not only as a place to transfer knowledge, but also to transfer values, traditions and lifestyle. Students, teachers and employees are guided and encouraged to know, understand, practice and enjoy Islam as a real guide to life, not just theory. So it can be concluded that the planned program is in accordance with the objectives of the current Islamic religious education curriculum.